An Integrative Literature Review of University-Based Early Childhood Education and Care Centres within Early Childhood Teacher Education Settings - Pihanperä Meri; Lepistö Jaana; Ruokonen Inkeri (MDPI, 2022)
This research is an integrative literature review regarding the variety of university-based early childhood education and care (ECEC) centre models. This research focuses on those models that collaborate closely with early childhood (EC) teacher education programmes. The data were gathered from three different databases: ERIC (Ebscohost), Education Research Complete (Ebscohost) and ProQuest Central by using six different search terms. A total of 2766 publications were found. Based on the inclusion criteria, 40 publications were included in a data analysis. These publications consisted of descriptions of 53 different models regarding the collaboration between ECEC centres and universities. Two out of three models (n = 34) were university-based ECEC centres that collaborated closely with EC teacher education programmes by implementing various collaborations in education and research in their daily work. Outreach efforts were also implemented. This research invites EC teacher education programmes and ECEC centres for international collaboration and further research on this topic.